FUNKCJONOWANIE NAZW WŁASNYCH W JĘZYKU POTOCZNYM NOWORUSKICH - Kiklewicz, Aleksander (Acta Neophilologica, 2010)
The present study discusses the pragmatic function of language as realized by proper names in colloquial speech of New Russians who in the 90’s of the 20th century became a new industrial elite in the post-Soviet Russia. Specifically, a type of a sociolect with distinct secrecy features is put to analysis; the secrecy parameter makes the language of New Russians resemble jargon. The linguistic phenomenon discussed is the more interesting as the use of proper names in the language of New Russians violates the informative principle of language interaction. It neglects the cooperation principle, the quantity and the relevance postulates, in particular. The expansion of proper names, most of which refer to brand names or brand-name products, is intentionally used by subjects of communication: first, to realize the deictic function, which indicates the cultural community and the membership within a given social group/stratum; second, to realize the sociative function, which indicates the social structure and manifests solidarity or dominance/superiority towards the addressee. In addition, the expansion of proper names constitutes a characteristic feature of postmodernism.